Analisis Reaksi Pasar Modal Asia Tenggara pada Situasi Pandemi Covid-19 Gelombang Dua (Varian Delta) - Ifan Wicaksana Siregar; Eka Yulianti; Esi Fitriani Komara (Jurnal Bisnis dan Manajemen, 2022)
The objective of this study is to analyze the reaction of Southeast Asian capital markets to the second wave of the Covid-19 pandemic, in this case the Delta Variant. This study uses a quantitative research approach with descriptive analysis and comparative methods. The population in this study is the capital markets of Southeast Asian countries. Furthermore, the sampling technique is non-probability sampling, samples that meet the criteria are the capital markets of Indonesia, Malaysia, Singapore and Thailand. The results showed that based on the one sample T-test, there were abnormal returns in all Southeast Asian countries sampled for the second wave of Covid-19. However, the results show a different response from each country. The countries of Indonesia, Malaysia and Singapore show that investors in the capital markets of these countries can still benefit from positive abnormal returns on investments made as long as they make careful and mature decisions. The positive response at the start of the Delta variant's appearance could be due to investor confidence regarding the government's Covid-19 disaster mitigation. Meanwhile in Thailand, after the event date showed a negative response to the second wave of Covid-19. In addition, the presence of abnormal returns indicates that the market is efficient in the semi-strong form in terms of information in all the countries studied.